Khiyar Al-majlis (option of withdrawal before parting) in sale contract contemporary applications - Rahman, Md. Habib ur; Amanullah, Muhammad; Mohiuddin, Mohammad (Research Center for Islamic Economics, 2017)
This paper aims to study and analyze the notion of khiyar al-majlis from the viewpoints of prominent Schools of Islamic law. Khiyar al-majlis refers to an option for both contracting parties either to revoke or to continue with the contract before departing from the contracting session. This option is made lawful in Islamic law to ensure the absolute consent of the parties to the agreement and to give them adequate time to think carefully about the conclusion of the contract. However, the Hanafi and Maliki Schools do not advocate khiyar al-majlis, they advocate khiyar al-qabul (option of acceptance) instead. This study prefers the validity of khiyar al-majlis and discusses its applications. This is a qualitative study and classical references of the prominent Schools of Islamic law have been employed as the primary sources of the study. The study posits that in the case of a face to face contract khiyar al-majlis might be practical. But, in the case of online or distant contracts it is not practical because it would be difficult to determine whether the parties are continuing the session or not. Thus, in online contracts khiyar al-qabul is more practical and hence after making an offer and acceptance the contract is concluded, though the contracting session is prolonged.